2000
DOI: 10.1007/pl00000710
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of xanthine oxidase by liquiritigenin and isoliquiritigenin isolated from Sinofranchetia chinensis

Abstract: The methanol extract of the stem of Sinofranchetia inhibited the activity of xanthine oxidase in vitro. Bioassay-guided purification led to the isolation ofliquiritigenin and isoliquiritigenin as the main xanthine oxidase inhibitors. This inhibition of enzyme activity was found to be dose dependent, with an IC50 value of approximately 49.3 microM for liquiritigenin and 55.8 microM for isoliquiritigenin. Lineweaver-Burk transformation of the inhibition data indicated that the inhibition was of a mixed type for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
90
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(98 citation statements)
references
References 25 publications
4
90
0
3
Order By: Relevance
“…The well-known commercial XOD inhibitor is allopurinol. Although it has been used in clinical applications largely, the use of it can cause severe side effects such as hypersensitivity syndrome, Stevens Johnson syndrome, renal toxicity, allergy and skin problems [7][8][9]. Thus, there is a need to develop new XOD inhibitors which are safer and more effective than the currently used drugs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The well-known commercial XOD inhibitor is allopurinol. Although it has been used in clinical applications largely, the use of it can cause severe side effects such as hypersensitivity syndrome, Stevens Johnson syndrome, renal toxicity, allergy and skin problems [7][8][9]. Thus, there is a need to develop new XOD inhibitors which are safer and more effective than the currently used drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there is a need to develop new XOD inhibitors which are safer and more effective than the currently used drugs. It might be possible to use XOD inhibitors for the treatment of hepatitis and brain tumor where it was determined that the activity of XOD is increased [8,10]. Moreover, it was reported that XOD has a significant role in many diseases such as cardiovascular disorders, inflammations, chronic heart failure [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The flavonoids have aroused considerable interest recently because of their potential beneficial effects on human health; they have been reported to be antioxidants, antimicrobials, free radical scavengers, and metal chelators, and to have anti-allergic, anti-inflammatory, anti-tumor, anti-viral, and anti-bacterial properties. [2][3][4][5][6][7][8][9][10][11][12][13][14][15] Since flavonoids are an ubiquitous part of the human diet, their effects on human health are of interest. The study of health effects of flavonoids demands that sensitive methods be developed for their determination and quantifications.…”
Section: Introductionmentioning
confidence: 99%
“…Por exemplo, este composto exibiu atividade no músculo cardíaco (WEGENER et al, 1997), atividade antioxidante (PRACHAYASITTIKUL et al, 2008), efeito inibitório da xantina oxidase (KONG et al, 2000) e tirosinase (ZHENG et al, 2008), além de inibir a proliferação e induzir a apoptose em hepatoma humano (HSU et al, 2005). Também diminuiu a produção de prostaglandinas e óxido nítrico em macrófagos de rato (TAKAHASHI et al, 2004) e apresentou uma potente atividade inibitória de células cancerígenas de próstata (JUNG et al, 2006).…”
Section: Isolamento Dos Compostos Com Atividade Antibacterianaunclassified